(untitled) (Studia Prawnicze / The Legal Studies, 1980)
This study deals with the theory of the optimum process of administrating justice, discussed from the point of view of the theory of management with the elements of cybernetics. In par one the Author presents a general character and the subject-matter of the theory of the optimum process of administrating justice. In part two he analyses terms such as „optimum" and „efficacy" of the process of administrating justice. As for part three, it presents the components of the optimum process of administrating justice. The Author includes here: 1) social value of the process of administrating justice, understood as a relation between the administration of justice and social needs; 2) setting useful aims in front of the administration of justice; 3) reaching the appointed aims which constitutes efficacy in the narrow sense; 4) organization of the process of reaching the appointed aims with the help of a given system (rational use of human resources, financial funds, ’technics, information, etc.); 5) organization of the process of reaching the appointed aims of the administration of justice with the help of so called „measures of external environement".